Answers

2016-04-13T23:41:35+05:30
2016-04-14T11:30:04+05:30
x - \frac{1}{x} = 5

(x - \frac{1}{x} )^{3} = 5^{3}

x^{3} - (\frac{1}{x})^{3} - 3 . x^{2}. \frac{1}{x} + 3x (\frac{1}{x})^{2} = 125

x^{3} - \frac{1}{x^{3}} - 3 . x + 3 .\frac{1}{x} = 125

x^{3} - \frac{1}{x^{3}} - 3 . x + \frac{3}{x} = 125

x^{3} - \frac{1}{x^{3}} - 3 ( x - \frac{1}{x} )= 125\\x^{3} - \frac{1}{x^{3}} - 3 ( 5 )= 125

x^{3} - \frac{1}{x^{3}} = 125 +15

x^{3} - \frac{1}{x^{3}} = 140


Note: (a-b)³ = a³ - b³ +3a²b +3ab²
0